2019
DOI: 10.1016/j.prevetmed.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, phylogenetic and evolutionary analysis of porcine deltacoronavirus in Henan province, China

Abstract: A B S T R A C TPorcine deltacoronavirus (PDCoV) is a novel porcine enteric coronavirus that causes diarrhea, vomiting and dehydration in piglets. This newly virus has spread rapidly and has caused serious economic losses for pig industry since the outbreak in USA in 2014. In this study, 430 faecal and intestinal samples (143 faecal samples and 287 intestinal samples) were collected from individual pigs with diarrhea and 211 serum samples were also collected from the sows with mild diarrhea in 17 regions in Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
3
39
0
4
Order By: Relevance
“…PDCoV has been detected in many countries, and previous researches showed that the prevalence of PDCoV was mainly focus on suckling piglets with the mortality rate from 40 to 80% [14,15]. PDCoV was reported in Ohio of U.S.A. in February 2014 that with diarrhea in sows and piglets [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDCoV has been detected in many countries, and previous researches showed that the prevalence of PDCoV was mainly focus on suckling piglets with the mortality rate from 40 to 80% [14,15]. PDCoV was reported in Ohio of U.S.A. in February 2014 that with diarrhea in sows and piglets [4].…”
Section: Discussionmentioning
confidence: 99%
“…PDCoV could cause acute diarrhea, vomiting, dehydration and even lead to death in nursing piglets, with the main lesion of villous atrophy in intestines [10][11][12][13]. The prevalence of PDCoV in Henan province of China was about 23.49%, and up to 36.43% in suckling piglets [14,15]. Infected sows usually did not show obviously clinical signs so that the PDCoV detection in sows was often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The USA/Japan/South Korea lineage has a worldwide distribution (Jang et al, 2017;Nelson et al, 2019;Niederwerder and Hesse, 2018;Perez-Rivera et al, 2019;Suzuki et al, 2018). The China lineage has been the predominant lineage in China since 2014 Zhang et al, 2019a). S protein-based phylogenetic trees showed that 7 strains belonging to the China lineage were classified into a minor branch with CHN-HG-2017.…”
Section: Novel Amino Acid Deletions or Insertions Were Detected In Thmentioning
confidence: 99%
“…Porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), and porcine rotavirus (PoRV) are the most common viral agents causing piglet diarrhea [2]. Moreover, porcine deltacoronavirus (PDCoV), since first reported in 2009, has become an important cause of newborn piglet diarrhea [3][4][5][6][7][8][9]. Sometimes, mixed infections in clinics are frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Like TGEV, PEDV can cause severe enteritis in newborn piglets, but has higher mortality rate that may reach 100% during epidemics [12,13]. PDCoV, as a newly emerging porcine intestinal coronavirus, can also cause enteritis and severe diarrhea in piglets [9], leading to numerous economic losses for farmers in China. Its infection appears to be clinically milder with lower neonatal mortality rate of 30-40% compared to typical PEDV infection.…”
Section: Introductionmentioning
confidence: 99%